The Influences of Participative Organizational Climate and Self-Leadership on Innovative Behavior and the Roles of Job Involvement and Proactive Personality: A Survey in the Context of SMEs in Izmir - BÜLBÜL, SEÇİL (ELSEVIER SCIENCE BV, 2013)
Participative organizational climate and self-leadership have been subject to so many studies examining the innovative behavior in organizations in literature. Besides organizational climate and self-leadership, job involvement and personality traits are emphasized as another individual factors that have roles in innovative behavior of the employees in literature. Within the framework of individual workplace attitudes and personality traits, this study focuses on the notion that job involvement and proactive personality as among the individual factors that may affect innovative behavior moderate the relationship between participative organizational climate and innovative behavior. The survey of this study is conducted on 400 employees of 40 Small and Medium Sized Enterprises (SME's) operating in different industries in Izmir-Turkey, in 2012. The obtained data from the questionnaires are analyzed through the SPSS statistical packaged software. Analyses results revealed that all dimensions of participative organizational climate (socio-political support, participative work environment, access to resources, access to information) and self-leadership are directly and positively related with employees' innovative behavior and job involvement and proactive personality moderate the relationship between participative organizational climate and innovative behavior. (C) 2013 Published by Elsevier Ltd. Selection and peer-review under responsibility of The Second International Conference on Leadership, Technology and Innovation Management
Keywords: Participative organizational climate; self-leadership; innovative behavior; job involvement; proctive pesonality; Small and Medium Sized Enterprises; DECISION-MAKING; WORK; RECONSIDERATION; IMPLEMENTATION; SATISFACTION; PERFORMANCE; CREATIVITY; MANAGEMENT; WORKPLACE; MODEL